Prevention of Human Trafficking with AMP Model with based vilage education - Katinah, Kuswandi; Sembodo, Sigit Priyo; Surachmad, Surachmad (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
This study offers a framework for the prevention of human trafficking using the action means purpose (AMP) model in "Kampunge arek surobayo ". This model has the goal of creating an educative, safe, comfortable, friendly, healthy, creative living environment (kampong) and literacy for the process of child development in community support that guarantees the fulfillment of children's rights and seeks optimal protection of children. KAS KP raised AREK's local culture, which became the spirit of the village, including togetherness, mutual cooperation, ownership, help, tolerance and concern for the environment, especially in the growth and development of children around it and the development of a variety of activities in 6 (six) variables include; educative village, foster village, safe village, healthy village, innovative creative village and literacy village.